Estudo da microestrutura do concreto com adição de cinza de casca de arroz residual sem beneficiamento - Duart, Marcelo Adriano (2008)
The use of mineral adition in concrete is a widely studied theme for several researchers that looking for features like: save cement for reducing costs, durability improvement to increase mechanical strenght and use of industrial wastes for reducing environmental pollution. This study intend to analize the microstructure of concretes mixtures with ungrounded residual rice husk ash addition without burn control unground (RHAN), like a partial cement substitute in conventional concrete for reducing costs, since cement is the most expensive component, and the use RHAN avoiding dumping on environment like a ground and water pollutant. Five different concrete mixtures proportions: 2 mixes of RHAN, with 15% and 25% of partial cement substitution, 2 mixes of ground RHA (RHAM), with 15% and 25% of partial cement substitution, for comparison, and a control design, withouth adition. All concrete disigns were developed for 3 water/binder relationships (0,45, 0,55 e 0,65), 15 differents concrete design in total, for ages 28 and 91 days, were done. Tests like: axial compressive strenght, percentual of chemically combined water, mercury intrusion porosimetry,X-ray difraction and image analysis by scanning eletronic microscope (SEM) combined energy dispersive spectroscopy (EDS) were done. Tests results proved that RHA use is feasible for 15% of substitution of cement by RHAN, since concretes had values of compressive strenght few smaller than control concrete values, at 28 days, however higher than it at 91 days. Because of pozolanic reaction and filler efect combination, of RHAN and RHAM particles, concrete with RHA adition had microstructural changes like: size pore refinement, total porosity reduction and calcium silicate hydrate (C-S-H) formation through pozolanic reaction. RHA Inert particles created nucleation sites improving hydrate crystals formation.